2021
DOI: 10.24191/ij.v8i0.100
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of Factors Affecting Financial Distress: Analysis Among PN17 Companies in Bursa Malaysia

Abstract: Financial distress is a condition of problems in corporate financing, in which there is a means of inability to pay to a creditor and is at risk of bankruptcy in the future. Those publicly listed companies having financial problems and any related issues will fall under Practice Note 17 (PN17). To have a better understanding, this study has aimed to examine the factors affecting financial distress among the PN17 companies in Bursa Malaysia for ten years of analysis, using data from 2008 to 2017. A total of 154… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…The study on the influence of liquidity, leverage, and profitability ratio on financial distress by Fatimah et al (2019) found liquidity did not affect financial distress, while leverage had a positive and significant effect on financial distress. Manaf et al (2020) investigated the factors that contribute to financial distress among the PN17 companies in Bursa Malaysia. The study found that liquidity, firm size, and leverage had a significant impact on financial distress, while profitability and sales growth had the opposite effect.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The study on the influence of liquidity, leverage, and profitability ratio on financial distress by Fatimah et al (2019) found liquidity did not affect financial distress, while leverage had a positive and significant effect on financial distress. Manaf et al (2020) investigated the factors that contribute to financial distress among the PN17 companies in Bursa Malaysia. The study found that liquidity, firm size, and leverage had a significant impact on financial distress, while profitability and sales growth had the opposite effect.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Companies facing financial distress encounter economic challenges such as insufficient capital or equity. In Malaysia, a financially distressed company is classified as a PN17 Company (Manaf et al, 2020). The PN17 refers to Practice Note 17, which is a regulatory framework employed by Bursa Malaysia, the Malaysian Stock Exchange (Manaf et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In Malaysia, a financially distressed company is classified as a PN17 Company (Manaf et al, 2020). The PN17 refers to Practice Note 17, which is a regulatory framework employed by Bursa Malaysia, the Malaysian Stock Exchange (Manaf et al, 2020). It classifies financially distressed companies failing to meet minimum capital, equity, or core business criteria.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Malaysia, companies that falls under the financial distress are called practice Note 17 (PN 17) companies. These companies are protected by section 276 of the company Act 1965 and monitored or checked by regulatory body towards predicting and addressing bankruptcy (Manaf et al, 2020). Based on that, the said PN17 companies have to deliver their reports to the board in order to secure approval for restructuring and maintaining their status in the list of companies (Manaf et al, 2020).…”
Section: Introductionmentioning
confidence: 99%